Oral buccoadhesive films of ondansetron: Development and evaluation - Kumria, Rachna; Gupta, Vishant; Bansal, Sanjay; Wadhwa, Jyoti; B Nair, Anroop (International Journal of Pharmaceutical Investigation, 2013)
Introduction: Difficulty or inability in swallowing tablets/capsules during or after chemotherapy is common due to chemotherapy induced nausea and vomiting in patients. Buccoadhesive films of ondansetron hydrochloride were prepared for the prevention and treatment of chemotherapy‑induced emesis. Films of varying polymeric composition were prepared in order to facilitate initial as well as prolonged drug release that could take care of acute as well as delayed emesis. Materials and Methods: Mucoadhesive films were prepared using polymers such as hydroxypropyl methylcellulose (HPMC) E5, HPMC K100, and Eudragit® NE 30 D. The effect of concentration of these polymers on physical properties and drug release were studied. All the films were prepared by solvent casting method. In another part of the study, the effect of drug concentration on physical and mucoadhesive properties of film were assessed, keeping the polymer concentration fixed. Results: Films containing HPMC showed good mucoadhesion. Increasing the concentration of Eudragit® NE 30 D in the films retarded drug release and increased residence time, however, reduced mucoadhesion. At a fixed polymer concentration and ratio, films prepared using an increased drug content showed an increased mucoadhesion. Conclusion: Films prepared using HPMC E5 (1000 mg), HPMC K100 (500 mg), and Eudragit® NE 30 D (750 mg) provided initial rapid followed by sustained drug release over a period of 6 h. Given the promising results, the study concluded that the developed buccal films have the potential to release ondansetron required for chemotherapy induced acute and delayed emesis.
Keywords: Buccoadhesive; Eudragit®; hydroxypropyl methylcellulose; mucoadhesion; ondansetron; permeation